Problems in the management of a geriatric patient with colorectal cancer based on ICNP® - a case report - Gierosz, Daria; Mess, Eleonora (Journal of Education, Health and Sport, 2022)
Colorectal cancer is the third most common malignancy among the population. The average incidence is over 65 years of age. The majority of cases are not hereditary and sporadic infections predominate. The aim of this study was to determine the most important nursing problems of a patient with colorectal cancer , as well as to recognize his bio-psycho-social situation. Using interview technique, physical examination, observation and research tools such as standardized scales and indicators. This allowed to prepare and implement a holistic nursing proces. The most important nursing problems in the analyzed case were: hypoxia of the patient, limitation of independence as a result of weakness of the organism, pain in the bony button, dehydration, occurrence of skin changes in the stoma area, anxiety and lack of acceptance of the disease state. There were also knowledge deficits regarding dietary recommendations, as well as the effects of nicotine on the human body.